(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This study aims to analyze the dynamic relationship between macroeconomic variables and banking activity indicators in the Commercial Bank of Syria over the period 2000–2023, using quarterly data. The independent variables include economic growth, inflation rate, exchange rate, and interest rate, while the dependent variables are return on assets, return on equity, and the loan-to-deposit ratio. The study adopts both the descriptive-analytical and quantitative econometric approaches. Phillips–Perron unit root test, Johansen cointegration test, and the Vector Error Correction Model were employed. The results show that all variables are stationary at the first difference and that five cointegrating relationships exist among them, confirming the presence of a long-run equilibrium relationship between macroeconomic variables and banking activity indicators. The findings also reveal that the interest rate was the most influential variable in banking indicators, while inflation had a dual effect depending on the indicator considered. In addition, the error correction coefficients indicate different speeds of adjustment toward long-run equilibrium. Overall, the results confirm that banking activity in the Commercial Bank remained strongly linked to fluctuations in macroeconomic environment.